Cytophotometric and flow cytometric DNA content of isolated glands in gastric neoplasia. Issue 4 (April 1995) - Kitayama, Y; Nakamura, S; Sugimura, H; Kino, I
Abstract : The gland isolation method was applied to various gastric lesions to measure DNA content by cytophotometry and flow cytometry for the first time. By incubating and agitating fresh specimens from surgically resected stomachs in calcium-magnesium free Hanks's balanced salt solution (CMFH) containing EDTA, many neoplastic glandular epithelial cells were successfully isolated from the stroma, and their characteristic three dimensional features were seen morphologically. The DNA content of pure nuclear suspensions of isolated glands was obtained by cytophotometry and flow cytometry staining with 4', 6-diamino-2-phenylindole dihydrochloride (DAPI) and propidium iodide, respectively. Compared with histological grading, the frequency of the DNA aneuploidy of cancer with moderate or poor differentiation by cytophotometry (75%) was significantly higher than that of well differentiated cancer (25%), but the histological typing of gastric cancer DNA frequency were not correlated. This method allowed us to detect small aneuploid peaks by flow cytometry, which were previously masked by contaminating interstitial cells. The frequency of DNA aneuploidy detected by flow cytometry (87.5%) was higher than detected by cytophotometry (58.3%). The results of these studies shows the feasibility of this technique for analysing the DNA content of various lesions of the stomach.